Analysis of precipitation and recharge of aquifers in Tota and Ibagué (Colombia) from stable isotopes (18O and 2H) - Jorge Eliecer Mariño-Martínez; Andrés Martínez-Sánchez (Revista Facultad de Ingeniería, 2018)
Identifying the hydraulic connection between the area of recharge and the area of discharge in aquifers is only possible by using tracers; the 18O and 2H isotopes have proven to be good tracers to determine such hydraulic connection. It is assumed that in Ibagué and Lake Tota the recharge of the aquifers is given by two processes: vertical infiltration and precipitation, and infiltration in the high mountains followed by regional permeation that reaches the aquifers in the lower part. In Tota, the delta (δ) values of 18O are lower in the higher part than in the lower part: in the higher area, the values are close to -10 ‰, while in the lower area they are close to -3‰. In Ibagué, the delta values (δ) of 18O are also higher in the lower part: in the upper area the values are between -8 and -11 ‰, while in the lower area are between -7 and -9 ‰. In both cases, the isotopic difference between the upper and the lower areas could indicate that not all the water recharge in the lower area comes from precipitation in the high mountains, but that additional recharge can be the product of precipitation and infiltration in the lower part.